Reproductive traits and factors affecting the size at maturity of Cancer pagurus across Northern Europe. (18th July 2016) - Haig, Jodie A.; Bakke, Snorre; Bell, Michael C.; Bloor, Isobel S. M.; Cohen, Mike; Coleman, Matthew; Dignan, Samuel; Kaiser, Michel J.; Pantin, Julia R.; Roach, Michael; Salomonsen, Harriet; Tully, Oliver
Abstract : In this article, we undertake the first broad-scale, cross-institutional collaboration to collect data on the size at maturity and reproductive strategy of the commercially fished decapod crab species, Cancer pagurus . Using identical methodology and temporal sampling, morphometric and physiological estimates of size at maturity were undertaken using 1806 crabs sampled from populations in the seas off Ireland, the Isle of Man, Scotland, Wales, England, and Norway. Additionally body condition, prevalence of external parasites, black spot disease, and the hepatosomatic index (HSI, hepatopancreas weight as a percentage of total tissue weight), and gonadosomatic index (GSI, gonad weight as a percentage of total tissue weight) were estimated for some populations. C. pagurus appears to use a "capitalist" reproductive strategy, relying on previously accumulated energy to use through the reproductive season. Crabs displaying black spot disease had significantly lower HSI values, taking into account that HSI decreases with each progressive reproductive stage. Male crabs with poor body condition and black spot disease displayed greater GSI values. Though this pattern was regionally variable, it indicates that, in some cases, physical stress may induce greater investment into reproductive resources. Based on the carapace width (CW) at which 50% of the sampled population was physiologically mature (CW50 ), estimates of size at first maturity varied between sampled populations in the range 97–117 mm CW in females and 59–106 mm CW in males. The CW50 estimates reported here are smaller than previously reported values for C. pagurus populations. However, the variety of laboratory and statistical methodologies used in published studies prevent absolute comparisons with our results. We discuss the benefits of developing a standardized methodology for size at maturity research and the need for greater collaboration in fisheries research to achieve goals set under the European Union's Data Collection Framework for this species.